Sinecatechins ointment for the treatment of warts in children. Issue 1 (31st August 2018) - Deeb, Maya; Levy, Rebecca; Pope, Elena; Lara‐Corrales, Irene
Abstract: Background: Sinecatechins ointment, a green tea derivative, is a novel agent approved for the treatment of anogenital warts in immunocompetent adults and has been reported to be effective in treating extragenital warts as well. Data are lacking in children. We sought to determine the efficacy and tolerability of sinecatechins ointment for treating warts in children. Methods: A retrospective cohort study was conducted of children with anogenital and/or extragenital warts treated with sinecatechins ointment for at least 1 month. The primary outcome was frequency of complete response (total resolution of warts at follow‐up). Secondary outcomes included frequency of partial response (reduction in number and/or size of warts) and adverse events. There was no control group for comparison. Results: Of 24 patients who met the inclusion criteria, 14 (58.3%) had anogenital warts, 7 (29.2%) had extragenital warts, and 3 (12.5%) had both anogenital and extragenital warts. Mean age at treatment initiation was 8.0 years (SD = 3.9). Median duration of warts at treatment initiation was 1.2 years (range 0.09‐12.62). Sixteen patients (66.7%) experienced a reduction in the number and/or size of the warts. Four patients (16.7%) had complete resolution. Median treatment duration was 4.5 months (range 0.6‐21.8) overall. Median time to complete resolution was 2.9 months (range 1.3‐7.7). Fifty‐four percent of patients used sinecatechins ointment as prescribed. Adverse events were limited to mild local irritation (7 patients; 29.2%). Conclusion: Sinecatechins ointment is a promising therapy for warts in children, and its use should be evaluated in prospective controlled clinical trials.